Effects of silicon on aluminum toxicity in upland rice plants - de Freitas, Lucas Barbosa; Fernandes, Dirceu Maximino [UNESP]; Maia, Suelen Cristina Mendonça; Fernandes, Adalton Mazetti [UNESP] (Springer Nature, 2017)
Aims: This study aimed to determine the capacity of Si to mitigate Al toxicity in upland rice plants (Oryza sativa L.) by evaluating plant growth and the Si and Al uptake kinetics. Methods: Plants were grown for 40 days, after which the Si and Al uptake kinetics (Cmin, Km and Imax) were analyzed. Then, the shoots and roots were separated, and the dry matter, root morphology and Si and Al concentration and accumulation in the plant were evaluated. Results: Aluminum decreased plant growth and the Si uptake capacity by decreasing the root growth and Si transport system efficiency in the upland rice roots (> Km and > Cmin). Silicon mitigated Al toxicity in the upland rice plants by decreasing Al transport to the plant shoots, although it did not reduce the Al uptake rate (Imax). Si treatment increased the growth of upland rice plant shoots grown in the presence of Al without influencing the root growth. The alleviation of Al toxicity by Si is more evident in the susceptible upland rice cultivar Maravilha. Conclusions: Silicon mitigated Al toxicity in the upland rice plants by decreasing Al transport to the plant shoots but did not reduce the Al uptake rate by roots.
Keywords: Root morphology; Silicon alleviation; Silicon uptake; Uptake kinetics